Chitosan Potential as Delivery Agent for S1 Gene from SARS-CoV-2 with pEGFP-N1 as its Vectors: Potensi Kitosan sebagai Sistem Penghantaran Gen S1 Virus SARS-CoV-2 dengan Vektor pEGFP-N1 - Kusumawati, Asmarani; Fahhlevi, Nabilah Adzra; Pratiwi, Rarastoeti; Jannah, Raudatul; Maulina, Nurina Tahta Afwi (Journal of Health (JoH), 2024)
Coronavirus Disease-19 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), this disease began to emerge at the end of 2019 and has become a pandemic to this day. Vaccination can play an important role to prevent the spread of the disease, so there are many vaccine developments, including DNA vaccines. Delivery systems such as chitosan can increase the effectiveness of vaccines. The purpose of this study was to optimize and evaluate the pEGFP-N1-S1 formula with a chitosan delivery system as a DNA vaccine candidate. Plasmids were cloned in E.coli DH5Î± and extracted for further evaluation with restriction enzymes and sequencing. The EGFP-N1-S1 plasmid was then formulated with chitosan nanoparticles with a mass ratio of Plasmid DNA:chitosan of 1:0.1; 1:0.2; 1:0.3; 1:0.4; 1:0.5; 1:0.6 and 1:0.7. The isolated plasmid has a concentration of 2182.32 ng/L and a purity of 1.911. Restriction results showed that the S1 gene (684 bp) was successfully inserted into the pEGFP-N1 plasmid (4813 bp). DNA:chitosan mass ratio of 1:0.6 is the optimal formulation for DNA to bind with chitosan perfectly.